2004
DOI: 10.1039/b315198k
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical synthesis of aragonite-type calcium carbonate with different morphologies

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
98
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 45 publications
3
98
2
Order By: Relevance
“…[13] Other reported ways to obtain aragonite include, for example, the transformation of amorphous calcium carbonate nanoparticles in reverse surfactant microemulsions, [14] by heat-induced precipitation onto self-assembled monolayers of anthracene-terminated thiol chains, [15] or by high-power ultrasonic irradiation at certain sound amplitudes. [16] Herein we report the simple synthesis of homogeneous aragonite crystals with structural complexity by applying the standard vapor diffusion method to particles of a hydrophilic block copolymer. [17] These particles are composed of a triblock copolymer, poly(diethylaminoethyl methacrylate)-b-poly(N-isopropylacrylamide)-b-poly(methacrylic acid) (PDEAEMA-b-PNIPAM-b-PMAA), in which the poly-(methacrylic acid) core is cross-linked by 1,3-diisopropylenebenzene.…”
mentioning
confidence: 99%
“…[13] Other reported ways to obtain aragonite include, for example, the transformation of amorphous calcium carbonate nanoparticles in reverse surfactant microemulsions, [14] by heat-induced precipitation onto self-assembled monolayers of anthracene-terminated thiol chains, [15] or by high-power ultrasonic irradiation at certain sound amplitudes. [16] Herein we report the simple synthesis of homogeneous aragonite crystals with structural complexity by applying the standard vapor diffusion method to particles of a hydrophilic block copolymer. [17] These particles are composed of a triblock copolymer, poly(diethylaminoethyl methacrylate)-b-poly(N-isopropylacrylamide)-b-poly(methacrylic acid) (PDEAEMA-b-PNIPAM-b-PMAA), in which the poly-(methacrylic acid) core is cross-linked by 1,3-diisopropylenebenzene.…”
mentioning
confidence: 99%
“…Figure 9(a) shows the XRD patterns of calcium carbonate precipitated with 5 ml GA/0.1, 0.2 and 0.3 mol of Ca 2+ at 95˚C. It is shown that at low initial concentration aragonite phase only was formed that appears from the peaks located at 2θ 26.19˚, 27.16˚, 37.8˚, 38.5˚ and 45.87˚) [56]. While the vaterite phase formed with increasing concentration of Ca 2+ with minor amount of calcite.…”
Section: Stability Of Vateritementioning
confidence: 99%
“…Figure 8(a) shows the XRD patterns of sample prepared with different dose of GA and incubated at ambient temp and at 95˚C. It shows that the calcium carbonate prepared in the absence of gum arabic at room temperature contains a mixture of calcite (40%) and vaterite (60%) but when prepared at 95˚C, the aragonite phase appeared (30%), located at 2θ 26.19˚, 27.16˚, 37.8˚, 38.5˚ and 45.87˚ [56] while calcite and vaterite content decreased to 48% and 22%, respectively. This is mainly due to transform of vaterite to calcite and to aragonite, where at elevated temperature which stabilized the aragonite phase [51].…”
Section: Stability Of Vateritementioning
confidence: 99%
“…[16] Furthermore, the concentrations of CO 3 2À ions and CO 2 can also influence the morphological evolution of calcium carbonate through changing its nucleation rates. [12,16] In our case, Ge micropatterns possess a suitable electrode overpotential for oxygen reduction, which can help create a premium rate of local pH change for the one-dimensional (1D) CaCO 3 growth. Moreover, a higher CO 2 concentration at the liquid-air interface is likely crucial in providing an appropriate nucleation rate for the growth of 1D CaCO 3 nanowires so that these wires can only be obtained on Ge micropatterns across the meniscus.…”
mentioning
confidence: 99%
“…One means to demonstrate the uniqueness and utility of such patterns is to evaluate their influence on the controlled growth of additional nanoscale materials such as calcium carbonate. Nanowires of this material have been prepared by several different methods, [9][10][11][12] and it has been proposed as a promising biomaterial for bone replacement and regeneration since it can be easily resorbed by osteoclasts (bone-resorbing cells), which subsequently undergo apoptosis and are then replaced by osteoblasts (bone-producing cells) to generate native bone. [13] To explore the possible patterning applications of Ge micropatterns in the field of biomineralization, such structures were used as templates to grow calcium carbonate nanowires via an electrochemical method using simulated body fluid (SBF) [14] or an aqueous CaCl 2 Á 2H 2 O and NaHCO 3 solution as electrolytes.…”
mentioning
confidence: 99%